Comparative analysis of methods of identification of skill needs on the labour market in transition to the low carbon economy 2011 (International Labour Organization GenevaCH, 2011)
Builds understanding of how to embark on a skills anticipation exercise for the low carbon economy, which is relevant for national, sectoral and enterprise level human resource strategies in mitigation and adaptation to climate change.
Keywords: SKILLS DEVELOPMENT